DRIVEN DROPLETS BY THERMOCAPILLARY EFFECT: QUADRATIC DEPENDENCE OF THE SURFACE TENSION ON THE TEMPERATURE - J. R. Mac Intyre; J. M. Gomba; C. A. Perazzo (Anales (Asociación Física Argentina), 2020)
We study the migration of droplets on a solid surface which is under a uniform temperature gradient. The present article focuses on partial wetting fluids which surface tension depends on the squared temperature. These type of liquids, called self-rewetting, show a complex dynamics and here we will compare with those liquids of linear dependence in temperature. Unlike to the latter ones, the droplet width increases with the time.